Surgical efficacy of minimally invasive thoracic discectomy. Issue 11 (November 2015) - Elhadi, Ali M.; Zehri, Aqib H.; Zaidi, Hasan A.; Almefty, Kaith K.; Preul, Mark C.; Theodore, Nicholas; Dickman, Curtis A.
Highlights Thoracoscopic spine surgery minimizes tissue injury during the approach. Single-level herniated discs with minor calcification are suitable for thoracoscopy. Presenting symptoms resolve in 79% of patients after thoracoscopic discectomy. Complications include intercostal neuralgia, atelectasis, and pleural effusion. Complication rates after thoracoscopic discectomy are acceptable (<25%).